Análise proteômica e morfológica em fígado de ratos submetidos à exposição ao chumbo e suplementados com ferro - Fernandes, Mileni da Silva (Universidade Federal de São Carlos, 2015)
Lead (Pb) is a heavy metal widely distributed in the environment, but it does not have any physiological role in the body. Due to its widespread use in the industry, it provides direct contamination of occupationally exposed people and, indirectly, through pollutants for the general. Thus, Pb contamination has become a public health problem. Studies have linked adverse health effects at low levels of Pb in the blood, even at concentrations below 10μg/dL. The effects range from cognitive impairment in children and peripheral neuropathy in adults, but there is little knowledge about its effects in the liver. It has been reported that iron (Fe) has a protective effect that can help in reducing the absorption of Pb in the body. In this sense, the aim of this study was to evaluate the protein profile and morphology in the liver of rats intoxicated by lead acetate (Pb(C2H3O2)2) submitted simultaneously to supplementation with iron sulfate (FeSO4) at 20 mg/Kg body weight. For this, 36 weanling male rats were divided into 6 groups (n=6) and treated for 6 weeks. The control group received deionized water; the first experimental group received deionized water and a solution of FeSO4 every two days; two experimental groups received 100 mg/L Pb(C2H3O2)2 in the drinking water and one of them was supplemented with FeSO4 every two days; two groups received 400 mg/L Pb(C2H3O2)2 in the drinking water, and one of them was supplemented with FeSO4 every two days. After euthanasia, blood samples and liver were collected for the analysis of Pb concentration by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Also, liver samples were collected for proteomic analysis using two-dimensional electrophoresis associated with MS (2D-PAGE-MS) and histomorphological analysis. The concentration of Pb in the blood and liver showed a dose-response effect with a reduction in 40-50% Pb in the groups supplemented with Fe (not significant). Histomorphological changes were observed in all intoxicated groups. Proteomic analysis identified 247 proteins with altered expression in relation to the control group. It was observed a decrease in antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxidase. The reduction of these enzymes leads to an increase of free radicals in the liver tissue and consequently to an in increase the levels of lipid peroxidation. The peroxidation affects the secretion of lipoproteins, mainly their release from the Golgi complex, which may have contributed to the changes observed in other proteins. The presence of Pb in some spots was confirmed by atomic absorption analysis, and this may have resulted in conformational changes that activate the protein degradation machinery. Based on the results, the present study highlights the deleterious role of Pb in the liver even at low dosage, and although Fe was associated with a reduced absorption of Pb, the results suggest that it should not be used as a prevention strategy to reduce the intoxication by Pb, since itself led to changes in the pattern of protein expression.
Keywords: Genética; Chumbo; Proteômica; Eletroforese bidimensional; Fígado; Lead; Proteomics; Two-dimensional electrophoresis; Liver; CIENCIAS BIOLOGICAS::GENETICA